Combination of bacteria-fungi in five formulations of carrier and its effectiveness on composting of corn stalk waste. Issue 1 (April 2020) - Faesal,; Djaenuddin, N.; Syafruddin,
Abstract: Bacteria and Fungi combination as decomposer in a fiew formulation and stored for several months after production. Research aim to study viability and effectivity of bacteria-fungi combining decomposer for maize waste composting. Material that using there were five carrier composition formula ie. BAGM (rice flour, charcoal flour, peat soil, and molasses), AAM (charcoal flour, jelly, and molasses), SAM (husk, jelly, and molases), BKM (rice flour, coconut water, and molasses), SGM (husk, peat soil, and molasses), and commercial biodecomposer Promi and EM4 as the check treatments. Isolate combination were using ie. bacteria+fungi BO(B7.1+O5) and EP(E7.7+P7). Results indicated that commonly carrier composition formula where tested was effective better than Promi and EM4 in maize waste composting. Carrier formula plus bio decomposer that consistently produce the better of compost after stored 12 and 24 WAP (weeks after production) i.e. combination of SAMEP, BAGmBO, SGMBEP and AAMEP and have opportunity to mass production for expansion.